2011
DOI: 10.1021/cg200947c
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Variation of Biogenic Calcite with Intracrystalline Organic Macromolecules

Abstract: The influence of intracrystalline organic macromolecules on the microstructure and properties of host crystals has been investigated by micro-and macroscopic analyses for several biogenic calcites: prisms in the outer layers of pearl oysters (Pinctada fucata), oysters (Crassostrea nippona), and pen shells (Atrina pectinata); folia in the inner layers of C. nippona and scallops (Patinopecten yessoensis); and coccoliths of Pleurochrysis carterae. Thermogravimetric analysis showed that the three prisms contain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…A similar pattern has been recently observed in the nacre of the mussel Perna [33]. Organic molecules occluded within the crystals and distributed around the boundaries of 200-300 nm crystalline domains (similar to the ones which we report here; figure 6a-c,e-i) were imaged with TEM in the calcites of the pterioidean Pinctada and in the ostreoidean Crassostrea [13,34]; the boundaries are characterized by small misorientations, in coincidence with small distortions of the crystal lattice. The same authors failed to find such patterns of misoriented domains in the calcite of the pinnoidean Atrina.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…A similar pattern has been recently observed in the nacre of the mussel Perna [33]. Organic molecules occluded within the crystals and distributed around the boundaries of 200-300 nm crystalline domains (similar to the ones which we report here; figure 6a-c,e-i) were imaged with TEM in the calcites of the pterioidean Pinctada and in the ostreoidean Crassostrea [13,34]; the boundaries are characterized by small misorientations, in coincidence with small distortions of the crystal lattice. The same authors failed to find such patterns of misoriented domains in the calcite of the pinnoidean Atrina.…”
Section: Discussionsupporting
confidence: 86%
“…They are anisotropic in shape, extending differently along diverse crystallographic directions [11]. These findings are in good agreement with the TEM observations [8,13] of intracrystalline submicrometre partitions with different diffraction contrasts, which were limited by discontinuously aligned biomacromolecules. Up to now, no data on the misorientation between adjacent nanodomains have been provided, although values less than 28 can be inferred from fig.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Crystallization in the shell, including that of organic matrices, produces an elaborate microstructure with micro-or nano-scale structures (Boggild 1930;Taylor and Kennedy 1969;Carter 1990;Carter and Hall 1990). Organic-inorganic microstructures reduce the area of the cleavage plane in the crystals and impart high mechanical strength and toughness to the shell (Kamat et al 2000;Okumura et al 2012). Previous reports have suggested that the organic matrices in the shell play key roles in regulating crystal nucleation, polymorphy, growth, morphology, and orientation in the calcification process (Lowenstam and Weiner 1989).…”
Section: Introductionmentioning
confidence: 99%